Studi Kesehatan Sungai Dengan Menggunakan Metode Biotilik Studi Kasus Di Sungai Pusur Kabupaten Klaten: River Health Study Using Biotic Method Case Study In Pusur River, Klaten District - Sugiyo, Siti Rohimah; Rawana, Rawana; Nugraha, Nanda Satya; Prijono, Agua (HUTAN TROPIKA, 2024)
Macroinvertebrates are organisms that live on the bottom of the water and have different levels of sensitivity to changes in conditions. The use of macroinvertebrates as indicators is due to their high sensitivity to changes in water quality, including the EPT group (Ephemeroptera, Plecoptera, and Trichoptera). In addition, the presence of EPT is influenced by the source of river pollution. This study was conducted at three monitoring stations (upstream, midstream, and downstream) located in Pusur River. Each station had ten repetitions of sampling, followed by the calculation of the macroinvertebrate assessment index value. The results of the study showed that at the Upstream station the level of pollution was light, at the Middle station the level of pollution was light, and at the Downstream station the level of pollution was moderate.